Development of a bow riser optimized for mass and stiffness using evolutionary computing - Edelmann-Nusser, J.; Heller, M.; Clement, S.; Vajna, S.; Jordan, A. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction In the Olympic competitions the so-called recurve bows are used. Figure 1 shows the most sizeable components of a recurve bow such as limbs, riser and stabilizers. Typical characteristics of a good riser are little weight and high stiffness (Haidn & Weineck, 2001). Hence a trend in the design of risers is to reduce weight. Methods The methods consist of the following parts: 1. An analysis of the loads that are applied to the riser of a drawn bow. 2. A static structural analysis of a riser using the loads of point 1. 3. Design of a parametric CAD model of the riser with 24 variable parameters. 4. Optimization of the parameters of the CAD model for mass and stiffness using evolutionary computing and selecting one model out of 1650. 5. The manufacturing of the riser with forged AS 28 using a computerized numerical control milling machine. 6. The test of the riser in practice by three archers of the German National Archery Team. Results The new riser has a mass of 871g at a quite similar stiffness as the riser with 1114g. I. e. the mass was reduced by 243g or by 22%. The three archers that tested the riser stated that the new riser suits them well and that it is not only very stiff and light but also damps the vibrations after the shot very well. Figure 2 shows a CAD model of the new riser, Figure 3 a complete bow with the new riser.